Study on correlation and path analysis between SPAD values and chlorophyll concentrations in three species of Berberidaceae leaves - LU Xiaoping; YANG Bingxian; XU Chanjuan; TIAN Jingkui; ZHANG Lin (浙江大学学报. 农业与生命科学版)
Determination of chlorophyll concentration has significance for photosynthesis and stress physiology since it is the main photosynthetic pigment in higher plant leaves. Previous researches have shown high correlation between leaf chlorophyll concentration and SPAD values, obtained by SPAD-502Plus chlorophyll meter. Path analysis also has been used for analyzing the direct effect and indirect effect among various independent variables and dependent variable.There exist large differences in leaf characteristics among three species of Berberidaceae i. e Mahonia bealei(Fort.) Carr., Mahonia fortunei (Lindl.) Fedde, and Nandina domestica. In order to study the correlation of SPAD values and chlorophyll concentration in these three species, the chlorophyll concentration was measured by SPAD-502Plus chlorophyll meter and ultraviolet spectrophotometer. The chlorophyll concentration was expressed as per unit leaf area or per unit leaf fresh mass respectively; a parameter SLW (ratio of leaf fresh mass and leaf area), was introduced to describe the characteristic of leaf thickness. The effects of both the leaf apparent characteristics and chlorophyll parameters on SPAD values were further investigated by path analysis. Moreover, the empirical relationships between the SPAD values and the concentration of chlorophyll a (Chla), chlorophyll b (Chlb) and total chlorophyll (TChl) were determined by a linear function, a second-order polynomials function, an exponential function and a power function to calculate the R2 decision value based optimal fitting curve.For all three species, when chlorophyll concentration was expressed as per unit leaf area, it showed significant correlation with SPAD values. The SPAD values showed higher correlation with the concentration of Chla than Chlb in M. bealei and M. fortunei, and the result was opposite in N. domestica. The positive correlation between parameter SLW and SPAD values was found among the three species and was significant in M. bealei and M. fortunei, which indicated that thick leaves contained higher chlorophyll concentration. Furthermore, SLW showed higher positive correlation with carotenoid (Car) than Chla, Chlb, TChl in all three species, which could be related to the stress resistance of Car; The path analysis led to two fold discoveries: 1) The concentration of Chla had the greatest impact on SPAD values; 2) The SPAD-502Plus chlorophyll meter could effectively eliminate the impact factors (e. g., leaf thickness). A non-linear relationship between SPAD values and chlorophyll concentration was indicated by the empirical equations; nevertheless, the optimal equations of Chla, Chlb, and TChl in M. bealei. were exponential function, while the power function of Chla, TChl and the second-order polynomials function of Chlb in M. fortunei and N. domestica were observed.The correlation between SPAD values and chlorophyll concentration in three different species of Berberidaceae indicats that the SPAD values can accurately reflect the chlorophyll concentration in higher plant leaves and the SPAD-502Plus chlorophyll meter can effectively eliminate the impact factors, so we propose that the SPAD-502Plus chlorophyll meter can be referred as a fast and nondestructive method to evaluate the chlorophyll concentration, and SPAD calibration curves shall commonly be parameterized as non-linear relationship.